Kendali Sistem Tegangan Baterai Peralatan 20 kV PT PLN Bontang - Zain, Abdul (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2022)
The protection system is essential in the 20 kV distribution network system. The 20 kV equipment control system is supplied from 2 sources: PT (Potential Transformer) and DC voltage supply (Battery). If the protection relay and mechanics do not get a DC voltage supply, it will have an impact on the equipment not being able to trip when there is a disturbance in the network. There is no DC voltage supply due to battery failure or damage. For this reason, it is necessary to operate the tool manually, which results in the normalization process taking longer because it takes time and long distances, so the duration of outages is even greater. In this study, a monitoring system for the battery of the equipment will be made where previously observations were made about the need for this tool. The method used by the tool uses the blynk application as a receiver of direct voltage and temperature measurement reports that are connected to the gsm module. As a microcontroller processes, Arduino Nano commands from intelligent phones, generating a measurement report from the battery. GSM SIM 900 module as a data receiver and sender in the system. This tool is easy to apply to the system because it does not require a sufficient additional voltage source from the battery. The results of this study become a solution for companies to improve their 20 kV. distribution network system.Â